NAILFOLD CAPILLAROSCOPY MAY BE A USEFUL TOOL FOR DETECTION OF MICROVASCULAR CHANGES IN PATIENTS WITH PSV - Yolbas, S.; Yildirim, A.; Dolasik, I.; Uz, B.; Koca, S. (Pergamon-Elsevier Science Ltd, 2014)
[Abstract Not Available]
5th International Eurasian Hematology Congress -- OCT 15-19, 2014 -- Antalya, TURKEY